FANTASI VERSUS IMITASI CASUS CYBERBULLYING DI MEDIA SOSIAL TINJAUAN MENJAGA HAK ANAK DALAM DUNIA PENDIDIKAN DI INDONESIA - Asmaunizar; Hasan Sazali; Nurul Fajri (Lembaga Sepercenter, 2025)
This study is a content analysis of YouTube videos depicting the feud between Nikita Mirzani and her daughter, Lolly. The aim of this study is to examine the impact of cyberbullying on students (adolescents) in the context of education in Indonesia. Cyberbullying is a form of bullying carried out through digital media and is prevalent among teenagers. This behaviour is influenced by various factors, both internal and external, including family, school, and community environments.The method used is a qualitative approach through content analysis and literature review, referencing various sources such as journals, books, and relevant documents. The research findings indicate that cyberbullying has a serious impact on students' learning processes, causing psychological disturbances such as stress, depression, and even suicidal tendencies.In the cases of Nikita Mirzani and Lolly, it is evident that children tend to imitate their mothers' controversial behaviour. This phenomenon indicates the exploitation of fantasy and public image for economic gain through digital platforms. However, such actions indirectly foster negative character traits among viewers, particularly teenagers, and have the potential to undermine educational, moral, and religious values of the nation.Therefore, such digital content requires serious attention as it negatively impacts children's development and the education system in Indonesia.